A new approach to the determination of tubular membrane capacitance: passive membrane electrical properties under reduced electrical conductivity of the extracellular solution - Šimurda, Jiří; Šimurdová, Milena; Švecová, Olga; Bébarová, Markéta (Pflugers Archiv, 2022)
The transverse-axial tubular system (tubular system) of cardiomyocytes plays a key role in excitation-contraction coupling. To determine the area of the tubular membrane in relation to the area of the surface membrane, indirect measurements through the determination of membrane capacitances are currently used in addition to microscopic methods. Unlike existing electrophysiological methods based on an irreversible procedure (osmotic shock), the proposed new approach uses a reversible short-term intermittent increase in the electrical resistance of the extracellular medium. The resulting increase in the lumen resistance of the tubular system makes it possible to determine separate capacitances of the tubular and surface membranes. Based on the analysis of the time course of the capacitive current, computational relations were derived to quantify the elements of the electrical equivalent circuit of the measured cardiomyocyte including both capacitances. The exposition to isotonic low-conductivity sucrose solution is reversible which is the main advantage of the proposed approach allowing repetitive measurements on the same cell under control and sucrose solutions. Experiments on rat ventricular cardiomyocytes (n = 20) resulted in the surface and tubular capacitance values implying the fraction of tubular capacitance/area of 0.327 ± 0.018. We conclude that the newly proposed method provides results comparable to the data obtained by the currently used detubulation method and, in addition, by being reversible, allows repeated evaluation of surface and tubular membrane parameters on the same cell.
Keywords: Novel method; elektrická vodivost; Sucrose; osmotický tlak; Cardiomyocyte; Rats; kardiomyocyty; spřažení excitace a kontrakce; zvířata; sacharosa; Tubular system; Electric Conductivity; Tubular membrane capacitance; Myocytes, Cardiac; krysa rodu Rattus; Excitation Contraction Coupling; Osmotic Pressure; Animals